"The Resources of Ibn Toloun Al-Salihi (died 953AH/ 1546AD) and His Method in His Book "Anbaa al-Umaraa li Anbaaa al-Wuzaraa - Zayan, Fayyad Ahmed (Journal of Humanities & Social Sciences, 2019)
One of the important things in reviving the glory of the Islamic nation is reviving the Arab and Islamic heritage which we should reveal and explore urgently because it is the identity of the Islamic nation in various religions, political, social, economic and cultural aspects of thought, culture and sciences, and one of the phases of heritage revival is the study of the many books written by the scholars of the Islamic nation and rich of Traditions, news and narrations, necessitating us to study these books and know their resources on which they were built and their authors' attitudes in writing. Ibn Toloun occupied a distinct place at that age due to his knowledge and religion. We addressed his valuable book "Anbaa al-Umaraa li Anbaa al-Wuzaraa" with analysis and study. The study started with an introduction and three sections including his biography and scientific status, his resources in this book, and his methodology and styles in displaying his scientific material. The study ended by the most important results and a list of endnotes and references.
Keywords: Ibn Tulun al-Salihi; book (Anbaa al-Amirs li Anbaa al-Wazira); methodology and resources